Comparision of Artificial Inteligence models used in computer games on the Unity platform - Szymon Kacprzyk; Vladyslav Hutsenko (Journal of Computer Sciences Institute)
Comparative analysis of artificial intelligence (AI) models used in computer games encompasses various approaches and techniques employed to create intelligent agents within gaming environments. Contemporary computer games utilize advanced AI systems to provide a more realistic and demanding experience for players. Three models were compared: Finite State Machine, AI Utility, and GOAP. The aim was to examine their effectiveness and applications in the context of creating intelligent agents in gaming environments. Modern games increasingly employ sophisticated AI models to ensure player immersion and maintain realism. During the research, each model was implemented, and the obtained results were subjected to detailed analysis.